PENERAPAN TEKNOLOGI WASTAFEL TANPA SENTUH DI TAMAN NGGIRLI DESA WISATA SRIMULYO, KABUPATEN BANTUL - Syamsiro, Mochamad; Wahyudi, Danang; Hasanah, Erni Ummi; Lantarsih, Retno; Prasetyanto, Hermawan (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
In response to the Covid-19 pandemic, a touchless portable sink has been developed. This innovative sink allows users to operate it by simply stomping on it with their feet, eliminating the need for hand contact. The implementation of touchless sink technology includes the design and production of touchless sinks, field testing of the equipment, and communication with the community and operators of the Wisata Taman Nggirli in Bantul. The initial phase of this program involves designing a touchless sink by utilizing engineering design programs. The second step proceeded with the manufacturing process, which took place in workshops located inside and outside the campus. Following that, the third phase involves conducting tests on the site and reaching out to the staffs of Taman Nggirli to engage them as users of this device. Participants were socialized through the introduction of touchless sinks, accompanied by an explanation of the distinction between touchless sinks and conventional sinks. Next, the participants are instructed on the operational mechanism of the touchless sink by demonstrating the use of a footrest located beneath the pedal. Finally, a testing of the device was conducted at the Taman Nggirli. Each participant eagerly attempted to use this touchless sink, one after another. Based on this testing, it is evident that the device functions effectively and may be utilized as intended.